Assessing opportunities for solar lanterns to improve educational outcomes in rural off-grid regions: Challenges and lessons from a randomized controlled trial - Ognen Stojanovski; Mark Thurber; George Muwowo; Frank A. Wolak; Kat Harrison (Asian Development Bank Institute (ADBI), 2018)
Solar lanterns are promoted across rural sub-Saharan Africa to improve both lighting in homes and educational outcomes. We undertake a randomized controlled trial in Zimba District, Zambia, to evaluate whether solar lanterns help children study more effectively and improve academic performance. Our research design accounts for potential income effects arising from the giveaways of lanterns and also "blinds" participants to the study's purpose. We find no evidence that receipt of a lantern improved performance on important national examinations (even though an ex post statistical power analysis demonstrates that the research should detect economically significant impacts, if present). We also do not observe impacts on self-reported study habits. Several features of Zimba District that are likely to exist in other developing regions appear to drive our results. First, flashlights are the dominant lighting source in rural Zambia rather than traditional options like kerosene lamps or candles. In such environments, solar lights may hold only limited appeal for prospective users. Second, our survey data suggests that other major barriers to educational attainment likely render improved energy access (whether through solar lanterns or otherwise) a relatively unimportant educational input.
Keywords: I20; O13; O12; 330